2022
DOI: 10.1021/acs.jchemed.2c00647
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry, Life Cycle Assessment, and Systems Thinking: An Integrated Comparative-Complementary Chemical Decision-Making Approach

Abstract: Chemistry students are passionate about using their learning to contribute toward a sustainable future, yet they feel unprepared to make green and sustainable practical decisions informed by industry-relevant tools. Most green chemistry metrics are mass-based, which do not estimate environmental impact or help address global socioeconomic challenges. We present the introduction of two complementary quantitative tools used in industry to compare greenness and environmental impacts of chemical reactions: (i) DOZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Even simple E -factor calculations make clear that the lower the need for solvents/chemistry per kg of recovered steel the better. 26 In addition, it was hoped that only partial devulcanization would be needed to clean the steel, again lowering the degree of chemistry needed. One recognizes, however, that each additional physical/chemical process adds to cost.…”
Section: Resultsmentioning
confidence: 99%
“…Even simple E -factor calculations make clear that the lower the need for solvents/chemistry per kg of recovered steel the better. 26 In addition, it was hoped that only partial devulcanization would be needed to clean the steel, again lowering the degree of chemistry needed. One recognizes, however, that each additional physical/chemical process adds to cost.…”
Section: Resultsmentioning
confidence: 99%
“…Employing LCA and green chemistry for chemical decision-making is also emphasized for a better environmental evaluation in another published work. 49 As we previously showed 21 and further explained in this study, an iterative approach can help with solvent selection since green chemistry researchers can investigate using in-process monitoring to assess essential parameters such as process yields and conduct process-based sustainability evaluation to ensure the alternative “green” alternative does not create unintended environmental, cost and chemical hazards.…”
Section: Resultsmentioning
confidence: 78%
“…Project-based learning (PBL) promotes inquiry-based learning and empowers students to synthesize previously learned knowledge taught through lectures, supplied information, or background material to solve a challenging problem, scaffold skills, and design experiments. , They learn critical, scientific, systems, and operational thinking also accessing research and technology to support the process of inquiry . Recent research has shown that PBL has been successfully integrated in lecture and laboratory in chemistry to encompass green, sustainable, circular, and life cycle thinking including considerations of chemical waste and socioeconomic and social justice to confront local and global challenges with a systems thinking lens. ,, …”
Section: Introductionmentioning
confidence: 99%
“…A strong emphasis on hazard and pollution prevention (principles 1–5, 8–9, and 11–12, AE, E-factor, and PMI, Table ) through intentional chemical design for avoiding waste generation, promoting safety, energy efficiency (principle 6), and life cycle thinking (principles 7 and 10) aligns seamlessly with the RAMP objectives (Table ) to provide a framework for effective chemical decision making. Although these principles have been successfully introduced into the chemistry curriculum for comparative green assessment between two synthetic processes, students have rarely been encouraged to become stakeholders in designing their own green chemistry experiment that allows them to achieve their existing laboratory learning outcomes without additional cognitive burden. For example, learning outcomes for the advanced organic chemistry experiments include an understanding of sequential multistep syntheses, monitored with at least thin layer chromatography (TLC), and characterization of the product using specialized spectroscopic techniques such Fourier transform infrared (FTIR), nuclear magnetic resonance (NMR) spectroscopies and mass spectrometry (MS) followed by interpretation of data and formal discussion in a lab report.…”
Section: Introductionmentioning
confidence: 99%